WOMEN ORGANIZATIONS, SECURITY AND PEACE-BUILDING IN NIGERIA: AN EXAMINATION OF THE PROGRAMMES AND ACTIVITIES OF EUNICE SPRING OF LIFE FOUNDATION - SAMUEL ENYI OTSAPA (International Studies Journal)
Not much literature exists on the contributions of women in security and peace-building in Nigeria – thus this article is a discussion of the contributions (present and potential) of women and women organizations in the security and peace-building process in Benue State by examining the programmes and activities of Eunice Spring of Life Foundation (ESLF); a Makurdi based non-governmental organization. The paper utilized both primary and secondary instruments to collect its data: questionnaire, books and journals. Findings show that through the advocacy and support of ESLF, nine (9) women were elected as chairpersons in nine (9) LGAs of the state and sensitizing and empowering youths led to an improvement in the security and peace of Benue communities. The study concluded that when women begin to contribute to the making of security and peace-building decisions and policies, security and peace in Nigeria and Benue State will improve. The paper recommends the promotion of women participation in security, conflict prevention, conflict management, conflict resolution and peace building.